РЕЛИГИОЗНО-СУФИЙСКИЕ МОТИВЫ АЗЕРБАЙДЖАНСКОЙ НАРОДНОЙ ПОЭЗИИ ХIX ВЕКА (на основе творчества народного творца поэта Мамедгусейна) - Дадашова, А. Ф. (Journal of Oriental Studies, 2016)
Мақалада ХIX ғасыр азербайжан халық поэзия- сындағы діни-сопылық сарындары туралы жазылған. One of the prominent representatives of Azerbaijan folk poetry in XIX is Poet Mammadhuseyn. He during all his creative life lived in Dashkend village of Goycha which is an eternal land of Azerbaijan which is under Armenian occupation at this moment and died in this place (1800- 1884). The biography of this prominent folk poet is connected with religious and divine values from the beginning. He was born in a sacred family which was a hearth of Seid. The poetry of this folk poet is very rich as a content.